The supremacy of love an agape-centered vision of Aristotelian virtue ethics - Silverman, Eric J., 1971- (Lexington Books, 2019)
The Supremacy of Love advocates an agape-centered vision of virtue ethics, combining traditional Aristotelian ethics with insights from Thomas Aquinas. It shows why virtue is good for the virtuous individual, reimagines impartiality so that it is compatible with close personal relationships, and has pluralistic cross-cultural applications.